The Role Of Brand Image, Trust And Brand Experience On Purchasing Decisions At The Janji Jiwa Malang Coffee Shop: The Role Of Brand Image, Trust And Brand Experience On Purchase Decision At Janji Jiwa Coffee Shop Malang - Nur Nadiya, Aeni; Sudiono Putri, Kartika Anggraeni (JURNAL EKBIS, 2023)
This research was conducted with the aim of describing purchasing decisions (Y) made by consumers which are influenced by the variables brand image (X1), brand trust (X2) and brand experience (X3) at the Janji Jiwa Coffee Shop in Malang City. The method used in this research is a descriptive quantitative method, by determining the consumers of the Janji Jiwa Coffee Shop in Malang City as the research population based on the phenomena that occur. Based on the predetermined population, 105 respondents were taken with the sampling technique used to determine sample characteristics using a purposive sampling technique. Meanwhile, data analysis efforts use multiple linear regression analysis methods. Based on the research that has been conducted, it was found that purchasing decisions at the Janji Jiwa Coffee Shop in Malang City are partially or simultaneously influenced by brand image, brand trust and brand experience. The more competitive the brand image is with competitors and is in line with the quality offered and is able to maintain the trust and experience of a brand, the more product purchases will occur at the Janji Jiwa Coffee Shop in Malang City.